Methods of Critiquing Ḍaʿīf and Mawḍūʿ Hadith: Concepts, Methodology, and Its Application in Qur’anic Exegesis - Taufiqurrohman Taufiqurrohman; Palahudin Palahudin; Ai Romlah (Program Magister Ilmu Al-Qur'an dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2026)
This study aims to examine the methods of hadith criticism applied to ḍaʿīf (weak) and mawḍūʿ (fabricated) hadiths in Qur’anic exegesis, as well as to formulate a systematic integrative model for selecting hadith narrations in interpretation. The main problem lies in the continued use of weak and fabricated hadiths in tafsir, which has the potential to distort the meaning of the Qur’an, while no comprehensive methodological model has yet been developed to integrate isnād (chain of transmission), matn (content), and the interpretive context. This research employs a qualitative approach with a library research design, collecting data from primary and secondary sources, which are then analyzed using content analysis and comparative analysis techniques. The findings reveal that hadith criticism in tafsir encompasses both isnād criticism and matn criticism; however, these approaches have not been implemented systematically. Concrete applications are found in Tafsir Ibn Kathir and Tafsir al-Manar, demonstrating that ḍaʿīf and mawḍūʿ hadiths can be identified through analysis of the chain of narrators and examination of the content. Therefore, this study proposes an integrative model that simultaneously combines isnād analysis, matn analysis, and the contextual framework of tafsir. This model is considered more comprehensive in safe-guarding the validity of Qur’anic interpretation and contributes methodologically to the development of tafsir studies grounded in critical and contextual hadith criticism